Establishing the Feasibility of Face Transplantation in Granulomatosis With Polyangiitis. Issue 7 (8th April 2016) - Hashem, A. M.; Hoffman, G. S.; Gastman, B.; Bernard, S.; Djohan, R.; Hendrickson, M.; Schwarz, G.; Doumit, G.; Gharb, B. B.; Rampazzo, A.; Zins, J. E.; Siemionow, M.; et al.
Abstract : Granulomatosis with polyangiitis (GPA; formerly Wegener's granulomatosis) is a rare vasculitis that commonly starts in the craniofacial region. We report a case that was masked by prior facial trauma and associated with pyoderma gangrenosum (PG). Disease progression and aggressive debridements led to severe facial tissue loss. The decision to perform a face transplant was controversial because of the risk of disease relapse on the facial allograft. We reviewed renal transplant outcomes in GPA for possible relevance. A PubMed search retrieved 29 studies. Patient and graft survival, relapse, morbidity, mortality, rejection and immunosuppression were assessed. Ten‐year patient survival and graft survival were 84.4% and 72.6%, respectively. GPA relapse occurred in 31.5%, and upper airway/ocular relapse occurred in 17.8% (resolved in 76.9%). Mortality was 12.3%. Acute and chronic rejection rates were 14.9% and 6.8%, respectively. Traditional posttransplant immunosuppression was effective. Our review suggests that GPA renal transplant outcomes are comparable to general renal transplant cohorts. Furthermore, transplanted GPA patients exhibit lower disease relapse secondary to lifelong immunosuppression. This supported our decision to perform a face transplant in this patient, which has been successful up to the present time (1‐year posttransplantation). Untreated GPA and PG are potential causes of worse surgical outcomes in the craniofacial region. Abstract : A cohort analysis of renal transplant outcome with autoimmune polyangiitis (Wegener's) revealed long‐term survival and decreased primary disease relapse, thereby supporting the near total face transplantation in a patient with craniofacial destruction secondary to autoimmune polyangiitis and pyoderma gangrenosum.